Polar nighttime chemistry produces intense reactive bromine events - Simpson, William R.; Frieß, Udo; Thomas, J. L.; Lampel, Johannes; Platt, Ulrich (Geophysical research letters, 2018)
By examining the origin of airmasses that arrive at Utqiaġvik (formerly Barrow), Alaska, soon after polar sunrise (late January/early February), we identified periods when air arriving at Utqiaġvik had previously resided primarily at higher latitudes in near total darkness. Upon illumination, these airmasses produced high concentrations of reactive bromine, which was detected by differential optical absorption spectroscopy as bromine monoxide (BrO). These observations are consistent with nighttime production of a photolabile reactive bromine precursor (e.g., Br2 or BrCl). A large polar night source of photolabile reactive bromine precursors would contribute seed reactive bromine to daytime reactive bromine events and could export reactive halogens to lower latitudes and the free troposphere.